Technology Diffusion: Any Further Evidence for Computer Industry? - POLAT, UMURCAN (SPRINGER, 2020)
This paper explores the technology diffusion specifically in computer industry for a panel of 18 countries between the period 1999 and 2011. Strong evidence is found for the existence of diffusion of computer technology through bilateral capital good flows. This study shows that knowledge dissemination arises as an important determinant of output in computer sector. Still, domestic research and development efforts of countries are found to be the leading contributing factors in all model specifications. Besides, among two subgroups, in diffusion of computer technology, it is observed that USA contributes more to the knowledge dissemination in the related industry relative to three Asian countries i.e., Chinese Taipei, Korea and Singapore.
Keywords: R&D spillover; Technology diffusion; Computer sector; RESEARCH-AND-DEVELOPMENT; INVESTMENT TRANSFER TECHNOLOGY; DEVELOPMENT SPILLOVERS; KNOWLEDGE SPILLOVERS; ECONOMIC-GROWTH; TRADE; PRODUCTIVITY; IMPORTS